Global overlooked multidimensional water scarcity - Wenfeng Liu; Zhonghao Fu; Michelle T. H. van Vliet; Kyle Frankel Davis; Philippe Ciais; Yuzhuang Bao; Yawei Bai; Taisheng Du; Shaozhong Kang; Zun Yin; Yu Fang; Yoshihide Wada (Proceedings of the National Academy of Sciences, 2025)
Freshwater resources are fundamental to supporting humanity, and measures of water scarcity have been critical for identifying where water requirements and water availability are imbalanced. Existing water scarcity metrics typically account for blue water withdrawals (i.e., from surface-/groundwater), while the contribution of green water (i.e., soil moisture) and water quality—dimensions with important implications for multiple societal sectors—to water scarcity remains unclear. Here, we introduce the concept of multidimensional water scarcity that explicitly assesses all three of these dimensions of water scarcity and evaluates their individual and combined effects. We find that 22 to 26% of the global land area and 58 to 64% of the global population are exposed to some form of water scarcity annually, with multidimensional (i.e., blue, green, and quality) water scarcity particularly high in India, China, and Pakistan. Examining seasonal water scarcity, we estimate that 5.9 billion people (or 80% of the world’s population in 2015) were exposed to at least one dimension of water scarcity for at least 1 mo per year and that 1-in-10 people (10%) were exposed to multidimensional water scarcity at least 1 mo per year. Our findings demonstrate that the challenges of water scarcity are far more widespread than previously understood. As such, our assessment provides a more holistic view of global water scarcity issues and points to overlooked scarcity where action needs to bring human pressure on freshwater resources into balance with water quantity and quality.